Strategi Penerjemahan Lisan Konsekutif dalam Misi Evaluasi Lapangan UNESCO di Geopark Kebumen - Aiesa Qonita Marati (Kementerian Sekretariat Negara Republik Indonesia, 2026)
Abstract In the past decade, Indonesia has experienced a significant rise in applications for UNESCO Global Geopark (UGGp) status, leading to a growing demand for interpreters during field evaluation missions. These missions involve complex interlinguistic communication between UNESCO evaluators and local stakeholders. Despite this, limited scholarly attention has been given to the role of interpreters and the strategies they employ in such contexts. This study aims to analyze the role of the interpreter and the consecutive interpreting strategies employed during the Kebumen Geopark field evaluation mission in Central Java. Adopting a qualitative descriptive design, the study examines audio recordings of interpreting activities among UNESCO evaluators, local site representatives, and the interpreter. The analysis is guided by the interpreting strategy framework proposed by Li (2015). The findings reveal that the interpreter played a crucial mediating role in facilitating effective communication across linguistic and cultural boundaries, particularly in conveying geopark-related concepts and development narratives. The interpreter consistently employed consecutive interpreting approach and utilized a range of strategies, including addition, omission, morpho-syntactic transformation, approximation, compression, and restructuring, often in combination within a single interpreting segment to enhance clarity, accuracy, and audience comprehension.